Isolated congenital microgastria in 4 years old child: a case report - S., Pramod; K., Ravikiran (International Surgery Journal, 2018)
Microgastria is a rare congenital anamoly. It was first reported in 1800s. It occurs in association with other anamolies. Common associated anomalies include asplenia, malrotation of intestine, upper limb anomalies, situs inversus. Isolated cases of Microgastria are very few in literature. Most cases of microgastria present during infancy. This is a report of a four year old child, eldest in litreature presenting with isolated microgastria. Child presented with vomiting, failure to thrive. Child underwent excision of stomach and oesophago-jejunostomy with pouch after initial stabilization. The child had an uneventful post-operative recovery.